THE CAUSES AND FACTORS OF THE CRISIS AND OCCUPATION OF THE KOKAND KHANATE - Sharifov Ehronbek Erkin oglu (American Journals Publishing, 2025)
This article explores the political instability and internal conflicts that led to the decline and eventual occupation of the Kokand Khanate by the Russian Empire in the 19th century. The text highlights a series of internal power struggles and assassinations following the death of Alimkhan in 1810, which created a volatile environment. Subsequent rulers, including Umarkhan, Muhammad Alikhan, and Sheralikhan, made attempts to consolidate power and expand the khanate's territory, yet their reigns were plagued by court intrigues and rebellions. The article details the devastating impact of these conflicts, particularly the intervention of the Bukhara Emirate and the rise of the Kipchak aristocracy under figures like Musulmonqul. This internal chaos significantly weakened the khanate, leaving it vulnerable to the expanding Russian Empire. The text concludes by describing the final Russian advance, the suppression of popular uprisings such as the Po'latkhan Rebellion, and the ultimate annexation of the territory, which was transformed into the Fergana.
Keywords: Kokand Khanate, Russian Occupation, Internal Conflict, Political Instability, Alimkhan, Umarkhan, Muhammad Alikhan, Fergana.